Analisis Permasalahan Perkembangan UMKM Terhadap Perekonomian di Indonesia - Asyifah Fauzah Delfira; Putri Yuliarman; Muhammad Baihaqi (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, contributing 61.07% to Gross Domestic Product (GDP) and absorbing 97% of the workforce. However, this sector still faces various challenges, both from internal factors such as limited capital, human resources, and access to technology, as well as external factors such as a less conducive business climate, inadequate infrastructure, and technological development. This study uses a qualitative method with a literature study approach to analyze the problems faced by MSMEs and find strategic solutions. The results of the study show that government support, optimization of access to financing, and utilization of digital technology are needed to increase the competitiveness of MSMEs so that they can continue to grow and make a greater contribution to national economic growth.